Estimating the optimum size of a tidal array at a multi-inlet system considering environmental and performance constraints - González-Gorbeña, Eduardo; Pacheco, André; Plomaritis, Theocharis A.; Ferreira, Óscar; Sequeira, Cláudia (Applied energy, 2018)
•A procedure for the optimisation of tidal array size through surrogate modelling is introduced.•Array size is defined by means of two design variables: number of rows and number of turbines per row.•Tidal array is placed in a channel of a multi-inlet costal lagoon with complex feedback mechanisms.•A numerical model is set-up and validated to assess effects of arrays in hydro- and morphodynamics.•Multi-objective optimisation models are formulated considering environmental constraints. This paper investigates the optimum tidal energy converter array density at a tidal inlet by applying surrogate-based optimisation. The SBO procedure comprises problem formulation, design of experiments, numerical simulations, surrogate model construction and constrained optimisation. This study presents an example for the Faro-Olhão Inlet in the Ria Formosa (Portugal), a potential site for tidal in-stream energy extraction. A 35 kW Evopod™ floating tidal energy converter from Oceanflow Energy Ltd. has been used for array size calculations considering two design variables: (1) number of array rows, and (2) number of tidal energy converter per row. Arrays up to 13 rows with 6–11 tidal energy converters each are studied to assess their impacts on array performance, inlets discharges and bathymetry changes. The analysis identified the positive/negative feedbacks between the two design variables in real case complex flow fields under variable bathymetry and channel morphology. The non-uniformity of tidal currents along the array region causes the variability of the resource in each row, as well as makes it difficult to predict the resultant array configuration interactions. Four different multi-objective optimisation models are formulated subject to a set of performance and environmental constraints. Results from the optimisation models imply that the largest array size that meets the environmental constraints is made of 5 rows with 6 tidal energy converter each and an overall capacity factor of 11.6% resulting in an energy production of 1.01 GWh year−1. On the other hand, a higher energy production (1.20 GWh year−1) is achieved by an optimum array configuration, made of 3 rows with 10 tidal energy converters per row, which maximises power output satisfying environmental and performance restrictions. This optimal configuration permits a good level of energy extraction while having a reduced effect on the hydrodynamic functioning of the multi-inlet system. These results prove the suitability and the potential wide use of the surrogate-based optimisation method to define array characteristics that enhance power production and at the same time respect the environmental surrounding conditions.